DEVELOPMENT OF FRAMEWORK FOR TIME DEPENDENT RELIABILITY ANALYSIS OF JACK-UP STRUCTURES - IDRIS, AHMAD (2018)
Due to the continuous demand for the use of jack-up in deeper, harsher and more hostile offshore environments, there is an increasing need for better analysis techniques that more accurately reflects the physical processes in their safety assessment